The Role of Intern Students in Improving Student Administrative Competence at BKAD NTB Province - Rosa Sapitri Sapitri; Safira Putri; Intan Leskantari; Laily Musyarofa; Mirnawati; Rahmad Hidayat (Yayasan Siti Widhatul Faeha, 2026)
Internship activities are a form of practice-based learning designed to strengthen students’ competencies, especially in the field of administration. This study aims to analyze the role of student interns in improving students’ administrative competencies during the internship program at the Regional Financial and Asset Management Agency (BKAD) of West Nusa Tenggara Province. The study employed a qualitative descriptive method with a participatory approach, where students were directly involved in administrative activities, while data were collected through observation, interviews, and documentation. The results show that student interns played an active role in supporting administrative tasks, including data entry, document management, and assisting in the preparation of financial reports. In conclusion, the direct involvement of students in workplace activities contributed positively to the enhancement of their knowledge, practical skills, and professional work attitudes. The implications of this study indicate that internship programs can serve as an effective strategy to bridge academic learning with professional practice while also supporting the efficiency of administrative work within government institutions.